Arabic- English Code-Switching in Arabic Digital Discourse Theories, Methods and Research Problems - Hadi Salim, Lect. Alyaa (Basra studies journal, 2026)
This critical review provides a comprehensive and systematic overview of studies that have addressed the phenomenon of code-switching between Arabic and English in Arabic digital discourse (from social media platforms and online comments to blogs, instant messages and internet forums) during the period from 2005 to 2024. The review incorporates the analysis of 60 peer-reviewed studies selected according to the PRISMA protocol from global academic databases, and addresses four main themes: the theoretical frameworks employed in the study of digital code-switching, the Structural and functional patterns documented– in Arabic-English digital discourse, the identity and ideological dimensions associated with the switch in cyberspace, and finally the research methods used and their suitability to the specificities of the digital environment. The review concludes that Arabic digital discourse offers an exceptionally rich field for –trans-languaging, surpassing in its complexity and specificity the traditional theoretical frameworks derived from face-to-face spoken discourse. There is a pressing need to develop analytical approaches tailored to the digital environment, taking into account the unique characteristics of multi-system digital writing and the nature of real-time and near-real-time electronic interaction.